Upper gastrointestinal endoscopy in rural setting: an experience of a trained general practitioner in himalayan region of Nepal - Dangal, Binod; KC, Archana (Journal of General Practice and Emergency Medicine of Nepal, 2024)
Introduction: Gastrointestinal disorders are very common in general population. Upper Gastrointestinal (UGI) Endoscopy plays an important role in evaluating oropharynx, esophagus, stomach and proximal duodenal problems. UGI endoscopy is utilized for various diagnostic and therapeutic purposes. Because patients in rural Nepal are primarily served by General Practitioners (GPs) and have limited access to specialists and endoscopes, a study was initiated to assess the spectrum of diseases, outcomes, and complications of UGI endoscopy performed by a trained GP in Tsho-Rolpa General Hospital, Dolakha, Nepal. Method: This study was retrospective observational study conducted at Tsho-Rolpa General Hospital, Dolakha, Nepal. The convenience sampling method was used. Records of UGI endoscopy book were reviewed and analyzed from Jan 2023 to Dec 2023. Data entry and descriptive analysis were done in SPSS version 25 and descriptive statistics were performed. Result: A total of 436 Upper Gastrointestinal Endoscopy was performed by a trained General Practitioner over a period of 1 year. Among them, 307 (70%) were females and 129 (30%) were males. The mean age of the population studied was 41.6 ±14.56 years. Patients of age group 35 to 44 years were one third. 61% (267) cases and had commonest problem of gastritis and interestingly 14% also had normal findings. Epigastric pain was the major complaint among 226 (52%) cases. And, 159 cases (36.5%) presented from Bhimeshor municipality of Dolakha where the hospital lies and 19 (4.3%) cases presented from other districts. No major complications were noted during and after the procedure. Conclusion: A trained general practitioner can perform upper gastrointestinal endoscopy in rural setting. Gastritis is the major finding with epigastric pain as a major complaint. Significant proportion of people had normal findings. Further research is needed to assess quality of endoscopy performed by GP in rural setting. General Practitioners need guidance from GI experts to consult cases and seek advice.